Financial Service Provider and Online Sexual Exploitation of Children: A Lacunae in Indonesia Legal Framework? - Nelson, Febby Mutiara; Santoso, Topo (Journal of Law and Legal Reform, 2025)
Online sexual abuse and exploitation of children is a serious global issue nowadays. In Indonesia, data from the Ministry of Women’s Empowerment and Child Protection (KemenPPA) shows that the number of reported child violence cases reached 24,158 in 2023. Of this total, sexual violence was the most common, with 10,932 cases. The key problem lies in the gap within the Legal Framework for addressing Child Sexual Exploitation in Indonesia. The issue is becoming more serious because the financial sector also plays a role, as perpetrators use financial means to carry out their actions. This has not been adequately addressed by Indonesia’s legal framework. Although Indonesia has prohibited and imposed penalties for perpetrators of child sexual exploitation and online sexual exploitation (for example, through the Criminal Code, Child Protection Law, Law on Sexual Violence, Pornography Law, and Electronic Information and Transactions Law), efforts to address the misuse of the financial sector by perpetrators have not been reflected in laws governing the financial services sector (such as the Indonesia Financial Services Authority Law, Banking Law, Indonesia Financial Services Authority Regulations, etc.). This paper, through a doctrinal research approach, examines the extent to which Indonesia’s legal framework addresses child sexual exploitation in accordance with international standards, conventions, trends, and developments. By analyzing how other countries—such as England, Wales, Sweden, the United States, and Australia—handle child sexual exploitation, particularly in relation to financial service providers, Indonesia can learn valuable lessons. In conclusion, this paper finds that Indonesia’s legal framework is insufficient to address child sexual exploitation and abuse involving financial means.